Nurses and Physicians Interprofessional Collaboration during COVID-19 Pandemic in a Maternity Outpatient Department: A Mixed Method Approach - Annama Mathews (17075127) (2023)
Objective The investigators aim to conduct mixed-method research to explore the Interprofessional Collaboration or IPC experience of both nurses and doctors in Women’s Wellness and Research Center or WWRC during the COVID-19 Pandemic. The IPC in OPD has made novel and dramatic changes in order to continue its operations during the pandemic; thus, new adaptive strategies were implemented which are worth exploring in this research.  Design Sequential Mixed-Method Research Design.  Method Using the Jefferson Scale of Attitude toward Interprofessional Collaboration (JeffSATIC), a cross-sectional online survey was conducted. The instrument is applicable to all health professions and allows group comparisons in different professional specialties. The tool comprises 20 items across two factors including working relationship and accountability. Seventy-five nurses and 83 doctors made up the 158 respondents who were drawn from a tertiary maternity facility in Doha, Qatar. The team also conducted series of Focused Group Discussions using open-ended questions to gain more in-depth understanding about their experience. The SPSS Version 26 was used to examine the data that were exported from SurveyMonkey, and multiple regression analysis was used to identify the predictors. Thematic analysis was done for the qualitative data. Both findings from the statistical and thematic analyst were mixed to gain provide comprehensive description and insights about IPC. Results The results show the IPC mean score for physicians (M= 103.56) was higher than nurses (M=63.00) including matters on working relationship (M= 60.86) and accountability (M= 42.71). Comparably, the reported IPC mean score (M= 84.21) during pandemic was lower than data from Australia (M=114) and USA (M= 119) without pandemic. Moreover, both Clinical Experience and Educational Attainment are the significant predictors (p-value <0.05) for doctors while Trainings and Clinical Experience were significant predictors (p-value <0.5) for nurses. Six themes were derived from thematic analysis which focuses on shared challenges, strengthening nurse-physician partnership, and innovations in communication. Conclusions The attitude of both nurses and doctors toward IPC during a pandemic is predicted by knowledge gained through training and education, and duration of clinical experience. The IPC strengthen their partnership as care providers despite of the challenges and new ways of delivering patient care. Based on the findings, strategic planning about enhancing knowledge, clinical skills, and strengthening partnerships with IPC towards better maternity care outcomes during pandemic is recommended.